ANALISIS SINTAKSIS KATA DASAR DALAM BAHASA BALI - I Gusti Ayu Agung Bintang Vitriani Kusuma (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This study aims to analyze the syntactic structure of basic words in Balinese and their role in the formation of phrases and sentences. Balinese, as a regional language rich in cultural values, has a unique grammatical system, one of which is the language levels (alus, madya, kepara) that influence the selection and use of basic words in communication. In this paper, a non-participatory and naturalistic observation method was used with data sources from remote observation and observing natural situations by collecting data in the form of listening to situations in the surrounding environment. This observation aims to map the level of understanding of students, educators, and the surrounding community regarding the syntactic aspects of basic words in Balinese and document analysis. The results of the study indicate that basic words in Balinese can function as nouns, verbs, adjectives, pronouns, adverbs, and function words. In addition, basic words play a role as the main element in the syntactic structure, filling the functions of subjects, predicates, objects, and adverbs. Morphological processes such as affixation, nasalization, and zeroization also influence the form and meaning of basic words in sentences. The syntax of Balinese also reflects the social and cultural structure of Balinese society, making this language not only a means of communication, but also a symbol of cultural identity.